If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = 2x + -3 + -5x Reorder the terms: 5x = -3 + 2x + -5x Combine like terms: 2x + -5x = -3x 5x = -3 + -3x Solving 5x = -3 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 5x + 3x = -3 + -3x + 3x Combine like terms: 5x + 3x = 8x 8x = -3 + -3x + 3x Combine like terms: -3x + 3x = 0 8x = -3 + 0 8x = -3 Divide each side by '8'. x = -0.375 Simplifying x = -0.375
| 2(x+5)+2x=-x+5(x+2) | | 5x^2+5y^2-2z^2-6xy=56 | | 5x^2+5y^2-2z^2-6xy-56=0 | | 2x(x+5)+2x=-x+5(x+2) | | 3/5x=1/15-2/3x | | e/8-20=105 | | 1/10-1/4 | | 5r-5s=35 | | 1/8=1/4a | | x(x-9)+17=3(4-x) | | https://cdn.edjin.com/upload/RESOURCE/IMAGE/26226.gif | | -4.9x^2+5x+9=0 | | 5m+3-7m-1=-19 | | 5m+3-7m-1=m-9 | | 8x+22=-78 | | 2cosx-tanx=secx | | 24x^2+16x+144=0 | | (4x+8)-(x+3)= | | -75/4225/2= | | 3x^3+2x+18=0 | | n-52=3/2 | | (5x^-9/6y^-6)^-3 | | 6r-11=2r-29 | | 0=x^2-20x+80 | | X^2=342 | | x^5=255 | | (5x-9/6y-6)-3 | | -13=5-2m | | 40+15+0.25=45+0.35x | | 13/195=1/5x | | -9(-5+3x)=21 | | a/3-a/9=2 |